(3GdJPjjd hGdJcejd aj TQM GdJSgjds - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf , (B745 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3JHJOF HHGH YWa GdHjGf, Hbhdg(B: (3gPG GdJGHY GdLGQj eLQi GdfYJ aj XghQ GdeJHhY s
(3BNQgG (B:s
(3hbO bGdhG VGQH VQGHkG, hGdajYGd ajg cGdaYdGJ ef aYdd hbGd GHf GdbWGY hjLF eUOQ aGYd Ydi eaGYdI haYGd hajYGd aXGgQ s
(3JSgjd GdahGFO hJcejd GdebGUO dGHf eGdc GdWGFj GdLjGfj GdeJhai (B672(3g`s
(3fSNI NGeSIs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs